The spinal nerves that constitute the brachial plexus in the red squirrel (Sciurus vulgaris) - Aydin, A. (Czech Academy Agricultural Sciences, 2011)
The brachial plexus in adult red squirrels (Sciurus vulgaris) was found to be formed by the rami ventralis of C5, C6, C7, C8. A thin branch of C5 and C6 constituted the cranial trunk, and the caudal trunk was formed completely by the rami ventralis of C7 and C8. Thus, in squirrels, the spinal nerves which form the brachial plexus and the joining of these spinal nerves to each other differ from other rodents and mammals.
Keywords: spinal nerves; rami ventralis; brachial plexus; red squirrels